Fractioning of soil organic carbon in three types of land uses on cattle farMON in San Miguel de Barranca, Puntarenas-Costa Rica - Ramos Veintimilla, Raúl A. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Mag. Sc) -- CATIE; Turrialba (Costa Rica), 2003